Digital Divide: A Bibliometric Approach to Existing Knowledge - Cruz Cárdenas, Jorge; Palacio Fierro, Andrés; Zabelina E.; Deyneka O.; Ramos Galarza, Carlos (My University, 2023)
The topic of digital divide - the gap between those who have and those who do not have access to digital technologies - is of growing interest for both public and private sectors. This interest is reflected in an increasing number of academic and scientific publications focused on the topic. This study presents an overview of the digital divide research using a bibliometric approach. Analyzing 9,523 documents from the Scopus database, this study found that 1) there has been an accelerated growth in the publication rate on digital divide since 2018; 2) digital divide is a multidisciplinary field, led by the United States and other developed countries and some emerging countries; 3) the dominant term used to refer to the field, as per our analysis of the relevant keywords, is "digital divide"; and 4) as per our analysis of the evolution of keywords' importance, while topics related to technologies were of interest several years ago, current interest revolves around the effects of the Covid-19 pandemic, the elderly, education, and healthcare access. © 2023 IEEE.
Keywords: engineering education; literature; science; science fiction; technologies